Nanomagnetism in early diagnosis and treatment of cancer: A narrative review (Research, Society and Development, 2024)
This review presents an analysis of nanomagnetism in the treatment and cure of cancer. The primary objective of this study was to investigate how magnetic nanoparticles can be optimized to maximize efficiency and safety in tumor treatment, while minimizing the side effects associated with conventional therapies. To achieve this, the study set forth the following detailed objectives: to discuss cancer, nanotechnology, and nanomagnetism; to examine nanomagnetism in cancer diagnosis; to investigate the mechanism of action of nanoparticles; to analyze advancements and challenges in clinical research; and to compare the efficacy and safety of these therapies with conventional ones. The methodology employed included a review of relevant literature and an evaluation of data from secondary sources. The study's findings indicated effective concentration of treatments in tumor tissue with minimized damage to healthy cells, concluding that magnetic nanoparticles hold significant promise for revolutionizing oncological treatments. The final considerations emphasize the importance of continuing research on long-term safety, multidisciplinary collaboration, and clinical regulation, which are crucial for expanding understanding and fostering future advances in clinical application.